Elucidating the regulatory mechanism of Swi1 prion in global transcription and stress responses - Zhiqiang Du (Nature Portfolio, 2020)
Abstract Transcriptional regulators are prevalent among identified prions in Saccharomyces cerevisiae, however, it is unclear how prions affect genome-wide transcription. We show here that the prion ([SWI +]) and mutant (swi1∆) forms of Swi1, a subunit of the SWI/SNF chromatin-remodeling complex, confer dramatically distinct transcriptomic profiles. In [SWI +] cells, genes encoding for 34 transcription factors (TFs) and 24 Swi1-interacting proteins can undergo transcriptional modifications. Several TFs show enhanced aggregation in [SWI +] cells. Further analyses suggest that such alterations are key factors in specifying the transcriptomic signatures of [SWI +] cells. Interestingly, swi1∆ and [SWI +] impose distinct and oftentimes opposite effects on cellular functions. Translation-associated activities, in particular, are significantly reduced in swi1∆ cells. Although both swi1∆ and [SWI +] cells are similarly sensitive to thermal, osmotic and drought stresses, harmful, neutral or beneficial effects were observed for a panel of tested chemical stressors. Further analyses suggest that the environmental stress response (ESR) is mechanistically different between swi1∆ and [SWI +] cells—stress-inducible ESR (iESR) are repressed by [SWI +] but unchanged by swi1∆ while stress-repressible ESR (rESR) are induced by [SWI +] but repressed by swi1∆. Our work thus demonstrates primarily gain-of-function outcomes through transcriptomic modifications by [SWI +] and highlights a prion-mediated regulation of transcription and phenotypes in yeast.